Influence of Bank Credits on the Nigerian Economy - Innocent, Idachaba Odekina; Ademola, Olukotun G.; Glory, Elam Wunako (American Economic & Social Review, 2019)
The aim of this study is to examine the influence of bank credits on the Nigerian economy using time series data covering the period from 1980 to 2017.Gross domestic product was used as proxy for the economy while credits to the private sector, public sector and prime lending rate were used as proxies of Banks credits. Unit root test was used to test stationary which reveals that all the variables were stationary at first difference. The regression analysis result shows that credit to the private sector have positive effect on Nigerian economy while credit to public sector and prime lending rate have negative effect on the Nigerian economy. The result of co-integration test presented reveals that there exist among the variables co-integration which means long-run analysis. It is recommended that, policy makers should focus attention on long-run policies to promote economic growth such as development of modern banking sector, efficient financial market, infrastructures.